Pengaruh Gaya Kepemimpinan Transformasional Dan Kualitas Kehidupan Kerja Terhadap Kepuasan Kerja - Chamid Alif, A’an Abdul; Sunaryo, Hadi; Saraswati, Ety (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine the influence of transformational leadership style, quality of work life on job satisfaction. The data method in this research uses a questionnaire with a sample size of 43 employees. The analytical method used in this research is multiple linear analysis with hypothesis testing using the F test and t test. Based on the results of this research, it shows that Transformational Leadership Style and Quality of Work Life simultaneously influence Job Satisfaction, then Transformational Leadership Style influences Job Satisfaction, and Quality of Work Life influences Job Satisfaction. Keywords: Transformational Leadership Style, Quality Of Work Life dan Job Satisfaction